PENGEMBANGAN MOTORIK HALUS ANAK MELALUI GERAK DAN LAGU DALAM PEMBELAJARAN DARING DI MASA PANDEMIK COVID 19 - Siti Kurniasih (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2021)
Abstract: This study is aimed at exploring the fine motor skills improvement process of group B students and investigating to what extend the processing result of fine motor skills can be improved through movements and songs of online learning during the COVID-19 pandemic. This study was a classroom action research using Kemmis and Mc. Taggart research model. This study was conducted in 2 cycles with 8 meetings in each cycle where every cycle consisted of the following steps: planning, action and observation, reflection. The sample of this study was 10 Group B students . The instruments used in this study was observational sheet of students activities using movements and songs. The data in this study were quantitative and qualitative data. Quantitative data were analyzed by using descriptive statistic to compare the result from the first and second cycle. While qualitative data from observation and interview were analyzed through the following steps: data reduction, data display and data verification. The results of this study show that there is the improvement of fine motor skills through movements and songs, proven by the fine motor skills mean score in pre-cycle which was 50,25 % improve tso 67,50 % in cycle I and keep increasing becoming 86,29 % in cycle II.